Additive Manufacturing of Stretchable Strain Sensors: Fabrication, Optimization and Application - Bastawrous, John Nady Shihat (AUC Knowledge Fountain, 2023)
In this project, a novel strain sensor design is fabricated employing different additive manufacturing techniques. The spring sensor's primary material is PLA-Like resin with a nanocomposite encapsulation layer as the functional material. The main principle of Straining the sensors results in a change in resistivity as the distances among the conductive carbon particles change according to the strain applied. Sensor fabrication consists of two parts: spring manufacturing and development of nanocomposite encapsulation The nanocomposite matrix is developed through the dispersion of Graphene and Carbon nanotubes in Thermoplastic Polyurethane through sonication and magnetic hotplate stirring. While the spring itself is manufactured by injection molding, the spring is dip-coated in the TPU-Carbon nanocomposite to fully develop the functional spring sensor. The novel sensor design, nanocomposite development, and fabrication processes optimization combine to maximize key performance indicators which are: high gauge factors and large extension percentages. This project reports a maximum gauge factor of 950 and an extension of 300% of the initial sensor length. These promising electrotechnical properties show great potential to be employed in numerous applications, in this report, respiration monitoring for preterm infants is discussed as the main challenge to be addressed. Wearable sensors for infant respiration monitoring face some challenges with low gauge factors and stretchability. The application of this sensor addresses the current problems in the electromechanical behavior of current wearable systems reported in the literature.